Functional role of inflammation in the surgical injury induced vascular remodeling of male albino rats - Song, X.; Li, L.; Wu, Y.; Zhang, L.; Li, X. (Cellular and Molecular Biology, 2017)
Our present study investigates the cellular and molecular inflammatory events in male albino rat arterial injury. Male albino rats were subjected to longitudinal incision and carotid artery clamping for the duration of 45 days. Heat shock protein (HSP) 27, HSP70, HSP47 and Nuclear Factor kappa B (NF-ÎºB) expressions were determined by qPCR and Western blot method. The morphology of vessel wall alteration was studied by the light microscopy. The expression of NF-ÎºB was found to be increased after ten days of carotid artery injury. The qPCR and Western blot analysis showed elevation in HSP47, HSP27, and HSP70 expression, ten days following the surgical injury. The neointima-formation and the media layer discontinuity were evidenced by light microscopy. The dendritic-like cells were in close contact with the lymphocytes. Our study reports that the surgical injury induces an inflammatory response through the increased NF-ÎºB and HSPs expression.